Muscle Injury Around the Shoulder - Jacob, J.; O'Connor, P.; Pass, B. (Seminars in Musculoskeletal Radiology, 2022)
Acute shoulder tendon and intra-articular injuries are common and their imaging well described. However, a subset of patients present with more unusual acute shoulder muscle injury. Of these, pectoralis major muscle injuries are encountered the most often and are increasingly prevalent due to a focus on personal fitness, particularly bench-press exercises. Other muscle injuries around the shoulder are rare. This article reviews the anatomy, mechanism of injury, and the imaging findings in relation to injuries of these muscles around the shoulder. We focus on pectoralis major injury but also review proximal triceps, latissimus dorsi, teres major, and deltoid muscle injuries, providing imaging examples.
Keywords: muscle injury; sports; magnetic resonance imaging; ultrasonography